Digital Place Branding for Coffee Ecotourism in West Lampung - Suprihatin Ali; Gia Subagja; Retno Yulita; Dadang Karya Bakti (Jurnal Terekam Jejak, 2024)
This research aims to investigate the conditions and prospective characteristics of the Kopi Rigis tourist village. The investigation was carried out in Rigis Jaya Village, Air Hitam District, West Lampung Regency. It was considered as one of the tourist villages in the district of West Lampung, the location of the study was chosen for a purpose. This research employs a qualitative method. According to the source, the data utilized in this study are either primary or secondary. Observations, interviews, and documenting procedures are used for data collection. The results indicate that Kampung Kopi Rigis is proficient at its branding operations. Kampung Kopi Rigis leverages internet media such as websites, WhatsApp, Instagram, and Facebook in the promotion of tourism spots. However, it is quite regrettable that the website belonging to Kampung Kopi Rigis is not being used adequately for promotional purposes. This is demonstrated by the website's broken features. In addition, this Rigis Coffee Village can be transformed into a sustainable tourist attraction by maximizing and balancing the economic, social and environmental values of its components.